An improved high-resolution method for quantitative separation of empty and filled AAV8 capsids by strong anion exchange HPLC - Schrecke, Samantha; McManus, Kevin; Moshfegh, Cassandra; Stone, Jessica; Nguyen, Thuy-Uyen; Rivas, Gustavo; Muhamed, Ismaeel; Mitchell, Daniel A. J. (Frontiers in Bioengineering and Biotechnology, 2024)
Cell and gene therapy (CGT) is a field of therapeutic medicine that aims to treat, prevent, and cure diseases using engineered cells (stem cells, immune cells, and differentiated adult or fetal cells), vectors [Adeno Associated Virus (AAV), Adeno Virus (AV), Herpes Simplex Virus (HSV), Baculo Virus (BV), Lenti Virus (LV), Retro Virus (RV), etc.], and other carriers [non-viral vectors, virus-like particles (VLP), Lipid Nano-Particles (LNP), etc.]. Among viral CGT vectors, adeno-associated viruses and lentiviruses (AAV and LV) are the most widely applied vector platforms. The presence of non-functional (empty or non-infectious) vectors that carry null or partial genes in the final drug product is classified as an impurity by the FDA. These impurities impair dosage accuracy and induce non-specific immunogenicity and variability in drug efficacy. These non-functional viral vectors in the drug product need to be elucidated following International Conference on Harmonization (ICH) guidelines for clinical manufacturing of the final drug product. This article showcases an ion-exchange chromatography (IEX) high-resolution method supporting ICH guidelines using commercially available AAV8 filled and empty capsids as reference standards. Our method successfully separated empty to full capsids with a resolution of 15 and sustained a linearity greater than 0.98 even under a wide range of empty or full viral particle concentrations (E+9 to E+13 vp/mL), which is an upgrade to other IEX capsid separation methods. The medium-throughput capacity and shorter sample processing time improve testing efficiency and save costs while delivering quality as value. The discussed method is a reliable and reproducible platform to precisely evaluate the presence of non-functional viral particles in AAV8 samples. Aligned with other orthogonal results, the method is a powerful tool to improve the quality of rAAV analytics.